Australia, the healthiest nation: death, hospital and cost savings of the Preventative Health Taskforce target reductions for alcohol, 2007 to 2020 - Chikritzhs, Tanya; Whetton, S.; Daube, Mike; Pascal, Richard; Evans, M. (Australasian Medical Journal Pty Ltd, 2010)
Background - The National Preventative Health Taskforce has set a 30% target reduction in the proportion of risky and high risk drinkers by 2020. This study estimated the potential saving in deaths, hospitalisations and associated economic cost savings to premature mortality and health of achieving the target. Method - Past national estimates of alcohol-attributable hospitalisations and deaths were used to forecast trends from 2007 to 2020. Estimated potential savings in deaths and hospitalisations were based on incremental decline in the prevalence of risky/high-risk drinking reaching a total of 30% by 2020 (about 2.3% per year). Associated economic costs of premature death were estimated using the Value of Statistical Life method (willingness to pay). Hospital costs were estimated from known trends in annual national costs for recent past years and taking inflation into account. Results - A 30% reduction in risky/high-risk drinkers would avoid an estimated 7,200 deaths and some 94,000 person-years-of-life lost due to premature death by 2020. The estimated benefit to the health sector would include 330,000 fewer hospitalisations and 1.5 million associated bed days. The net present value of these benefits is AUD 22.7 billion from deaths avoided and AUD 1.7 billion from fewer hospital separations totalling AUD 24.4 billion. Conclusion - The potential savings in premature deaths, health and associated financial costs of a 30% reduction in risky and high-risk drinking by 2020 across the Australian population are considerable.